The Role of Soluble 5’-Nucleotidases in the Conversion of Nucleotide Analogs: Metabolic and Therapeutic Aspects - C. Skladanowski, A. (Current Medicinal Chemistry, 2013)
A variety of anti-proliferative drugs is based on the structure of purine or pyrimidine nucleosides. These compounds, after phosphorylation, act as analogs of natural nucleotides. In vivo they are recognized by enzymes that transform them either into anti-metabolites targeted to the synthesis of DNA or RNA, or to inactive products of detoxification. 5’-Nucleotidases of different specificity and cellular localization can either remove the phosphate residue from the 5’- position of (deoxy)nucleotide or transfer it from nucleoside monophosphate onto other nucleosides. Such a nucleoside phosphotransferase activity also works with analogs of canonical nucleotides and nucleosides. The majority of nucleoside analogs is metabolized by intracellular cytoplasmic or mitochondrial 5’-nucleotidases and only few reactions proceed on the cell surface. This review summarizes our knowledge of cytoplasmic and mitochondrial forms of 5’-nucleotidases and focuses on their ability to dephosphorylate different analogs of canonical nucleoside 5’-monophosphates. The involvement of 5’-nucleotidases in the phosphotransfer reaction with some nucleoside analogs has been also presented. The importance of the reactions catalyzed by 5’-nucleotidases in clinical resistance to nucleoside-based drugs used in the treatment of cancer or viral diseases, as well as in activation of pro-drugs has been highlighted
Keywords: drug resistance